2022
DOI: 10.1097/iae.0000000000003404
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exudative Maculopathy and Bacillary Layer Detachment in Patients With Central Serous Chorioretinopathy After Photodynamic Therapy

Abstract: Photodynamic therapy–induced acute exudative maculopathy was frequent in chronic central serous chorioretinopathy. However, a self-resolving evolution and favorable prognosis were observed in most cases. There was no association between photodynamic therapy–induced acute exudative maculopathy and age, sex, or choroidal neovascularization but was associated with worse baseline visual acuity and choriocapillaris vessel occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…Our study also resulted that BCVA had decreased in the PAEM+ group 1 month after PDT, but the long-term effect has been still unknown. Fernandez-Vigo et al reported that PAEM did not affect the mean BCVA gain at 3 months after PDT in chronic CSC, so further investigation is warranted 26 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our study also resulted that BCVA had decreased in the PAEM+ group 1 month after PDT, but the long-term effect has been still unknown. Fernandez-Vigo et al reported that PAEM did not affect the mean BCVA gain at 3 months after PDT in chronic CSC, so further investigation is warranted 26 .…”
Section: Discussionmentioning
confidence: 94%
“…Some reports have shown that PAEM is more likely to occur in CNV, followed by PCV, and rarely in chronic CSC 24 , 27 , 28 . Recently, Fernandez-Vigo et al 26 reported that in 92 eyes with CSC PAEM was observed 28 eyes (30.4%) with the criteria that define PAEM as an increase of 50 µm or more in the SRF height 3 days after PDT. While this percentage seemed to be higher than in other previous studies, including ours as CSC, that study was included the patients with CNV, which may be the reason for the higher percentage despite in CSC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAEM occurs in an estimated 1.4-30.4% of patients treated with PDT. 33,34,37 It has been reported to occur in the setting of chronic CSCR, choroidal hemangioma, retinal capillary hemangioma, CNVM, nAMD, and PCV with the highest incidence reported in CSCR (30.4%) followed by PCV (8.45%) and nAMD (6.67%). 17,[30][31][32][33][34]36 In a 2020 report, Manayath et al described the risk factors for PAEM in a large cohort of 177 PDT treatments in 155 eyes.…”
Section: Prevalence and Disease Characteristicsmentioning
confidence: 99%